Dynamic load tests on the North-South axis cable-stayed bridge with a non-symmetric central pylon. (2017) - Ivorra, Salvador; Foti, Dora; Paparella, Francesco; Baeza, F. Javier
Abstract: The new cable-stayed bridge built for the North-South axis road of Bari in order to overpass the railway of RFI and Ferrotramviaria s.p.a. has been recently built and opened to the traffic. The bridge is 626 m long and the central cable-stayed bays have a total length of 225 m. They are supported by cables connected to a central upside down Y-shaped pylon. The peculiarity is that this column is about 60° rotated with respect to the axis of the bridge deck. A dynamic load tests was developed previously to open the bridge to conventional traffic. 26 piezoelectric accelerometers have been utilized in different positions of the cables-stayed bays to record the accelerations produced by environmental forces and by the impact produced by a loaded truck passing over a bump. Operational Modal Analysis has been applied by mean of Artemis software to determine the first fundamental frequencies and the mode shapes. The main frequency of this non-symmetric pylon is the main frequency of all the stayed bridge.